Peranan Ulama Kharismatik Memotivasi Prilaku Agamis Masyarakat Kota Palembang - Yuanita Sari Yuanita (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2021)
This thesis is entitled "The Role of Charismatic Ulama Motivating the Religious Behavior of Palembang City Community". The Role of Charismatic Ulama in Motivating the Religious Behavior of the Palembang City Community. ”The research method used was qualitative, with a descriptive approach. The  research focus on the great Ulama of South Sumatra Province K.H. Muhammad Zen Syukri, research subjects consisted of 4 people, namely 1 Member of the DPRD of South Sumatra Province Alfarenzi Panggarbesi, who was also assisted by Hj. Wanny Rivai as a student and adopted child of the late K.H. Zen Syukri, then Selamet, the administrator of Nurul Hidayah Mosque, and Siti who is the treasurer and administrator of the Muqimus Sunnah Islamic Boarding School which was founded by KH Zen Syukri. Data collection techniques are obtained through interview data, observation data, data documentation and literature study. Data analysis techniques, namely data reduction, display data, and conclusion verification. Based on the results of this study, it shows that the role of charismatic clerics in motivating the religious behavior of the people of Palembang City or in this case raised about the late K. H Zen Syukri as an object of research has been achieved in view of the four charismatic research indicators marked with. 1). Having great communication skills, especially in influencing the thoughts, feelings and behavior of others, thereby arousing a sense of admiration from the community towards him and easy to socialize so that other people feel sympathetic towards him. 2.) Having a calm attitude in facing everything in the face of all obstacles that occur even though you take personal risks. 3). Having a high self-confidence in doing good things.